The Origin of General Contracting in Siam - Sirikiatikul, Pinai (NAJUA: History of Architecture and Thai Architecture, 2022)
In Early Bangkok, the corvée system was the primary resource for government construction. The situation in the Siamese building activity started to change towards the end of the eighteenth century, as a result of the decline of the corvée system, the influx of Chinese migrant workers, and the arrival of capitalism in the building. However, at no time did the process of construction start to be separated from the process of design as in the 1870s when a system of general contracting was adopted for government construction for the first time. This paper set out by looking at the difficulties that the Siamese Government had in dealing with the shortage of labour and the ineffectiveness in supplying building materials under the corvée system and examines how the new system of general contracting, brought to this country by European contractors, offered a more organised way of building as an alternative to the Siamese Government. Unlike the Siamese’s ancient mode of building production, where the cost of the building was calculated after the completion, under the general contracting, the general contractor was able to estimate the total expense of the work, and made an agreement with the commissioner, in advance, and then became the one who took control over the building work and the responsibility for the outcome of the work. The clear-cut separation between the process of design and the process of execution caused by the new method of contracting gave rise to the problems with which this paper is concerned. How did the introduction of general contracting lead to the changes in the relation of building production? Based on the correspondence related to buildings and the investigation of contractual documents such as building contracts, estimations, drawings and specifications, the paper shows that, apart from other benefits, transferring the building tasks to the hands of the general contractor also helped the Government to get away from the long-standing problems of labour and material management. While this new way of building practice presented considerable advantages both to the commissioner and the contractors, it presented some Siamese officials like maekong (a director of works) and naichang (a building designer) with the significant risk of losing control over the construction of a building, including manpower under their control. The paper argues that in these changing circumstances, there were to emerge two significant developments in architectural practice that are still relevant today. Firstly, the initiation of contractual documents including estimations, working drawings, building specifications and contracts, as a new media through which the commissioner and general contractors officially communicated. Secondly, the establishment of an architect as a distinctive government position in the Public Works Department whose role focused largely on design processes, independent from processes of construction, as well as the production of drawings and specifications as a mechanism to control the quality of the construction work performed by contractors. The article ends by considering the importance of drawings as the new material products of the architectural practice through the design processes of Wat Rachithiwas’s rebuilding constructed at the end of King Chulalongkorn’s reign. The finding reported here will lead to a better understanding of the nineteenth-century professionalisation of contractors in Thailand's context.